Legal Analysis of the Decision on the Request for Guardianship by the State for Christianity: Analisis Yuridis Terhadap Putusan Permohonan Wali Negara Bagi Agama Kristen - Savier, Alem; Wahyudi, Eko (Universitas Muhammadiyah Sidoarjo, 2024)
General Background: Marriage in the Christian religion fundamentally differs from other traditions, notably in the absence of a legal requirement for a marriage guardian. Specific Background: Instead, the presence of a priest to officiate the ceremony is deemed sufficient. This distinction is often misunderstood, leading to legal ambiguities and misapplications. Knowledge Gap: Despite clear doctrinal guidelines, there persists a lack of awareness regarding the role of state-appointed guardians in Christian marriages, as evidenced by legal cases requesting such appointments. Aims: This study aims to analyze the necessity and implications of appointing a state guardian in Christian marriages through the examination of relevant legal cases in the Jombang District Court. Results: The study highlights two pivotal cases: Request Number 20/Pdt.P/1994/PN Jmb, which was granted, and Request Number 119/Pdt.P/2023/PN Jbg, which was withdrawn. Novelty: By juxtaposing these cases, the research underscores the inconsistencies and the resultant need for greater legal and doctrinal clarity. Implications: The findings advocate for enhanced educational efforts within both the Christian community and the broader public to mitigate legal misunderstandings and to streamline the judicial approach to marriage guardianship in Christian contexts. This research contributes to the discourse by elucidating the legal boundaries and ecclesiastical stipulations of Christian marriages, promoting informed judicial decisions and societal understanding. Highlights: Legal Ambiguity: Inconsistent court decisions on state guardians in Christian marriages. Educational Need: Urgent need for educating communities on marriage guardianship in Christianity. Judicial Clarity: Importance of clear legal guidelines to prevent misapplications. Keywords: State Guardian, Decision on Request, Christian Marriage, Legal Analysis, Religious Doctrine